Natural deep eutectic solvents as a green extraction of polyphenols from spent coffee ground with enhanced bioactivities - García-Roldán, Aitor; Piriou, Léa; Jauregi, Paula (Frontiers in Plant Science, 2023)
Conventional extraction techniques are usually based on highly pollutant and/or flammable organic solvents. Therefore, alternative environmentally friendly extraction methods are of particular interest for the recovery of bioactive compounds for their application as food ingredients and/or nutraceuticals. Natural deep eutectic solvents (NADES) are a green and nontoxic attractive alternative to hydroalcoholic extraction. NADES media primarily depends on the intermolecular interactions (hydrogen bonding) among their components to form an eutectic mixture with a much lower final melting point than its individual components. Examples of natural deep eutectic NADES solvents include aqueous solutions (25-50% water) of choline chloride, sugars and polyols. This study aimed at investigating the application of two NADES namely, betaine:triethylene glycol (Bet:TEG) and choline chloride:1,2-propanediol (Chol:Prop) as sustainable green solvents for the extraction of polyphenols from spend coffee ground (SCG), a by-product of coffee processing. In particular, the extraction yield and selectivity were evaluated and compared with conventional green extractions (hot water and a hydroalcoholic solution). In addition, the effect of NADES on the antioxidant and antimicrobial activity of the extracts was investigated. The main outcomes were: (i) NADES were as effective as other conventional green solvents in the extraction of polyphenols with the added advantage of operating at milder temperature conditions, without flammable solvents and with sustainable and natural compounds (ii) antimicrobial activity of the NADES extracts was 10 times higher than that of the ethanolic and aqueous extracts. Given the low toxicity of NADES they could be used as formulation aid for food ingredients.